pH controls spermatozoa motility in the Pacific oyster (Crassostrea gigas) - Boulais, Myrina; Suquet, Marc; Arsenault-Pernet, Eve Julie; Malo, Florent; Queau, Isabelle; Pignet, Patricia; Ratiskol, Dominique; Le Grand, Jacqueline; Huber, Matthias; Cosson, Jacky (Biology Open, 2018)
WOS:000429100500005 International audience Investigating the roles of chemical factors stimulating and inhibiting sperm motility is required to understand the mechanisms of spermatozoa movement. In this study, we described the composition of the seminal fluid (osmotic pressure, pH, and ions) and investigated the roles of these factors and salinity in initiating spermatozoa movement in the Pacific oyster, Crassostrea gigas. The acidic pH of the gonad (5.82 +/- 0.22) maintained sperm in the quiescent stage and initiation of flagellar movement was triggered by a sudden increase of spermatozoa external pH (pHe) when released in seawater (SW). At pH 6.4, percentage of motile spermatozoa was three times higher when they were activated in SW containing 30 mM NH4Cl, which alkalinizes internal pH (pHi) of spermatozoa, compared to NH4Cl-free SW, revealing the role of pHi in triggering sperm movement. Percentage of motile spermatozoa activated in Na+-free artificial seawater (ASW) was highly reduced compared to ASW, suggesting that change of pHi triggering sperm motility was mediated by a Na+/H+ exchanger. Motility and swimming speed were highest in salinities between 33.8 and 42.7%(within a range of 0 to 50%), and pH values above 7.5 (within a range of 4.5 to 9.5).